2011
DOI: 10.1021/jz200791c
|View full text |Cite
|
Sign up to set email alerts
|

Surface Propensities of Atmospherically Relevant Ions in Salt Solutions Revealed by Phase-Sensitive Sum Frequency Vibrational Spectroscopy

Abstract: Supporting Information: Experimental Details and Spectral Analysis NaCl (99.999% trace metals basis), KCl (99.999% trace metals basis), NaNO 3 (99.995% trace metals basis), NH 4 Cl (99.998% trace metals basis), Na 2 SO 4 (99.99% trace metals basis), and (NH 4 ) 2 SO 4(99.999% trace metals basis) were purchased from Sigma-Aldrich. NaCl, KCl and Na 2 SO 4 were baked at 500 o C before use. For the aqueous solutions, proper amount of salts were dissolved in ultra-pure distilled water (with resistivity of 18.3 MΩ/c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

39
201
3

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 132 publications
(243 citation statements)
references
References 29 publications
39
201
3
Order By: Relevance
“…In line with the results of spectroscopic experiments performed over much longer time scales, 36 we find that anions are effectively segregated as if those having larger propensities for the air-liquid interface are enriched in the thinner sectors of the stretched bags. In other words, ion gradients over the span of stretched bags approach those expected from equilibrium distribution considerations.…”
Section: Resultssupporting
confidence: 87%
“…In line with the results of spectroscopic experiments performed over much longer time scales, 36 we find that anions are effectively segregated as if those having larger propensities for the air-liquid interface are enriched in the thinner sectors of the stretched bags. In other words, ion gradients over the span of stretched bags approach those expected from equilibrium distribution considerations.…”
Section: Resultssupporting
confidence: 87%
“…This is borne out by the negative surface potential of most electrolyte solutions, 50, 51 by surface-specific spectroscopic studies, 34,[52][53][54] and by model calculations.…”
Section: Resultsmentioning
confidence: 99%
“…For example, surface tension increments (STIs; differences between the surface tension of a salt solution and that of neat water) of sodium salts at the same concentration decrease in the order: SO 4 2− > Cl − > Br − > NO 3 − > I − (15, 16). Molecular dynamics (MD) simulations have predicted that the propensity of anions to adsorb to the solution-vapor interface follows the Hofmeister series in reverse (7,14,17), and this prediction has largely been confirmed experimentally (14,(18)(19)(20)(21)(22). Moreover, MD simulations have shown that, with few exceptions [e.g., SO 4 2− in (NH 4 ) 2 SO 4 (23)], anions adsorb more strongly to the solution−air interface than their counter cations, and, consequently, electrical double layers are formed near the interface, with the anions residing in or near the topmost layer of the solution, and the cations residing below the anions (14,24,25).…”
mentioning
confidence: 89%
“…Moreover, MD simulations have shown that, with few exceptions [e.g., SO 4 2− in (NH 4 ) 2 SO 4 (23)], anions adsorb more strongly to the solution−air interface than their counter cations, and, consequently, electrical double layers are formed near the interface, with the anions residing in or near the topmost layer of the solution, and the cations residing below the anions (14,24,25). Surface potentials (26), phase-sensitive vibrational sum frequency generation (PS-VSFG) spectra (22,27,28), and X-ray photoelectron spectroscopic (XPS) data (19,(29)(30)(31)(32) are consistent with the double layer picture.Compared with anion-specific effects, cation-specific effects at the solution−air interface are generally observed to be relatively weak. For example, the concentration dependence of the STIs of LiCl, NaCl, and KCl are very similar (33).…”
mentioning
confidence: 99%
See 1 more Smart Citation